SEMANTIC ANALYSIS OF THE CONCEPT “WORK” IN RUSSIAN AND ENGLISH PROVERBS AND SAYINGS (World Bulletin of Social Sciences, 2024)
The article gives a semantic description of proverbs about work, reflecting the features of the mentality of the Russian and English people. Semantic analysis of proverbs and sayings makes it possible to identify three components of the concept “work”: the process of activity, the subject of activity, the result of work
Keywords: semantic analysis; proverbs; work